2019
DOI: 10.5606/kbbu.2019.60783
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperbaric oxygen on hyperglycemia-induced cochlear damage: An experimental study

Abstract: Bu çalışmada diabetes mellituslu sıçanlarda hiperglisemiye bağlı koklear hasarın hiperbarik oksijen terapisi (HBOT) ile tedavi edilip edilemeyeceği distorsiyon ürünü otoakustik emisyon (DÜOAE) ve histopatolojik analiz kullanılarak araştırıldı. Gereç ve Yöntemler: Çalışmaya 18 erkek albino Sprague Dawley sıçan (≥350 g ağırlığında, en az iki aylık) dahil edildi. Hayvanlar kontrol grubu (grup 1), streptozosin (STZ) ile indüklenmiş diyabet grubu (grup 2) ve STZ ile indüklenmiş diyabet+HBOT grubu (grup 3) olmak üze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Several studies have demonstrated that DM patients with SSNHL have more severe hearing loss and a poorer prognosis than those without DM, although few studies have evaluated the treatment of these patients, particularly using HBOT. A notable study of albino Sprague-Dawley rats found that hyperglycemia induced cochlear damage, and HBOT alleviated the histological changes associated with diabetes-induced cochlear damage 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that DM patients with SSNHL have more severe hearing loss and a poorer prognosis than those without DM, although few studies have evaluated the treatment of these patients, particularly using HBOT. A notable study of albino Sprague-Dawley rats found that hyperglycemia induced cochlear damage, and HBOT alleviated the histological changes associated with diabetes-induced cochlear damage 27 .…”
Section: Discussionmentioning
confidence: 99%